Colore senza nome - Brusatin, Manlio (Venice Marsilio, 2006)
‘Is Blank also a colour? Blank is a colour of the mind. The mind has a colour that we can never see because there is always some other colour passing through the mind and overlapping our gaze' Italo Calvino, 1985The author suggests a navigation between the techniques of evading and showing the work of art: from the darkness of the images that develop their possible meaning in time, to the ‘ buoyancy’ in the colours and the artist harlequin or clown, from the blindness in front of the colour, to the chromatic research carried out by the new visual arts, to end with the additional colours, which are born in our mind. Colour, therefore, speaks to us of how art is and how it could be made, even if it does not yet have a name, and it is this that allows us to search for it in dispersed forms, like a visible echo. Art, in order to last, must initially consign itself to oblivion: a necessary condition for it to be discovered as such. And therefore to exist. (Translated with Deepl.com)
Manlio Brusatin (1943) teaches at the Faculty of Design at the Milan Polytechnic and at the Faculty of Architecture in Alghero. He has collaborated on various Venice Biennales of the arts, architecture and theatre and has international experience on the subject of colour, a topic on which he has held lectures, conferences and seminars in Italian and foreign museums and universities. His numerous publications include the historical-critical trilogy on the arts Storia dei colori (Turin 1983, 22 editions), Storia delle linee (Turin 2001, 5 editions), Storia delle immagini (Turin 2002, 5 editions).
Keywords: Esthetics; Fine art